2010
DOI: 10.1107/s1744309110002204
|View full text |Cite
|
Sign up to set email alerts
|

Purification, crystallization and preliminary data analysis of FocB, a transcription factor regulating fimbrial adhesin expression in uropathogenicEscherichia coli

Abstract: The transcription factor FocB belongs to a family of regulators encoded by several different fimbriae gene clusters in uropathogenic Escherichia coli. Recent findings suggest that FocB-family proteins may form different protein-protein complexes and that they may exert both positive and negative effects on the transcription of fimbriae genes. However, little is known about the actual role and mode of action when these proteins interact with the fimbriae operons. The 109-amino-acid FocB transcription factor fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…As anticipated from CD measurements and secondary structure prediction software [27] (Fig. 2), the amino acid chain of FocB forms an all α‐helical structure that comprises five α‐helices: α1 (Asp12‐Ser21), α2 (30Glu‐Ser40), α3 (Asp45‐Gly58), α4 (Arg61‐Tyr68), and α5 (Asn71‐Tyr95) (Fig.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…As anticipated from CD measurements and secondary structure prediction software [27] (Fig. 2), the amino acid chain of FocB forms an all α‐helical structure that comprises five α‐helices: α1 (Asp12‐Ser21), α2 (30Glu‐Ser40), α3 (Asp45‐Gly58), α4 (Arg61‐Tyr68), and α5 (Asn71‐Tyr95) (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Cross‐linking and size exclusion chromatography studies showed that FocB forms predominantly dimers in solution [27]. Furthermore, the packing of molecules in the crystal structure suggests that FocB is dimeric.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations